Performansi Waiting Time di Pelabuhan Tanjung Priok - Muhammad Ikhza Maulana; Yulianti Keke; Tjetjep Karsafman Karsafman (Institut Transportasi dan Logistik Trisakti, 2020)
PT. Pelabuhan Indonesia II as an operator at Tanjung Priok port, which is the busiest port in Indonesia, seeks to improve guidance and delay services by implementing a Marine Operating System (MOS) which works by integrating ship service facilities and infrastructure, one of which is tugboats. This study aims to analyze and determine how much influence the implementation of the Marine Operating System (MOS) and the availability of tugs on Waiting Time performance. This research uses quantitative research of respondents in the Tanjung Priok Port Ship Service Division. Based on the analysis that has been done, it shows that there is a positive and significant influence by the implementation of the Marine Operating System (MOS) on Waiting Time performance, besides that the results of this analysis show that there is a significant and positive influence on the availability of tugs on Waiting Time Performance, and there is a significant and positive influence by the implementation of the Marine Operating System (MOS) and the availability of tugs simultaneously on Waiting Time Performance.